A ÚLTIMA CRISE: desde o colapso de Lehman Brothers até a questão da dívida pública europeia - Francesco Schettino (Universidade Federal do Maranhão, 2014)
This paper inquires on the causes, the evolution and the perspectives of the economic crisis since the collapse of Lehman Brothers, until the actuality, i.e. the debt crisis of the southern countries of European Union. By means of Marxian theoretical tools the article explains the reasons which this crisis can be considered as a typical capitalistic crisis, once that the overproduction and the relative fall of the profit rate are common factors in the prevalent part of the world. In this way we drastically exclude the interpretation of some researchers sustaining its financial nature assigning the responsibility to the behavior of a few number of capitals (rating agencies). Giving an interpretation of current evolution of the crisis by means of the intra-capitalistic battle, we show how the capital linked to the dollar, overthrew the main consequences of the crisis - originated in the U.S. in the ‘70s, in the twentieth century - on the EU countries.